The solution of a singular integral equation with some applications in potential theory - N. T. Shawagfeh (International Journal of Mathematics and Mathematical Sciences)
An analytical solution is derived for a singular integral equation which governs some twodimensional potential boundary value problems in a region exterior to n-infinite co-axial circular strips. An application in electrostatics is discussed.